72 Routine use of comprehensive genomic profiling to assess tumor mutational burden across a community health system. (10th December 2020) - Bifulco, Carlo; Weerasinghe, Roshanthi; Bapat, Bela; Dowdell, Alexa; Pindikuri, Shwetha; Reynolds, Sheila; Biery, Nancy; Ball, David; Campbell, Mary; Ward, Thomas; Stein, Alisha; Schroeder, Brock; et al.
Abstract : Background: Tumor mutational burden (TMB), defined as the average number of somatic mutations per megabase (mut/Mb) of DNA in tumor cells, has emerged as a predictive biomarker for response to immune checkpoint inhibitor (ICI) therapy. With more widespread adoption of comprehensive genomic profiling (CGP) assays in the clinic, it is now possible to routinely assess TMB across a wide variety of advanced cancers. Here we performed a retrospective study of routine TMB results assessed from CGP testing across a large community health system to reveal novel insights into the proportion of patients that may benefit from ICI treatment. Methods: Patients in the Providence St. Joseph Healthcare system diagnosed with advanced or metastatic solid tumors and tested for TMB using CGP tests (TruSight Oncology 500, research use only) between July 2019 and July 2020 were considered in this study. Deidentified electronic medical record data and CGP results were abstracted for downstream study. Results: A total of 1300 patients had one or more CGP tests with a TMB calculation. The median age of patients was 66 years, 51% were female, and 59% were white. TMB values ranged from 0–536 mutations per mut/Mb. Across tumor types, the proportion of patients with TMB ≥10 mut/Mb was 26% (n=341) and with TMB 5–9 mut/Mb was 27% (n=353). The proportion of patients with TMB ≥10 mut/Mb varied by tumor type: Melanoma (60%), NSCLC (42%), CRC (24%), pancreatic (5%). Of all the TMB-tested patients, 90 (7%) received IO therapy post testing. IO therapy use was highest among patients with TMB ≥10 mut/Mb (12%), followed by 7% with TMB of 5–9 mut/Mb, and 4% with TMB of 0–5 mut/Mb. Twenty-nine percent of TMB ≥10 also had high PD-L1 expression by IHC as compared to 8% of TMB <10. ICI therapy choice in this retrospective cohort appeared to be largely driven by other considerations (PD-L1 immunohistochemistry etc.) independent of TMB. Conclusions: A minority of TMB ≥10 patients assessed in this study received an ICI therapy, a result that is likely reflective of the lack of definitive guidelines for this emerging biomarker. As the adoption of TMB increases as a biomarker of immunotherapy response, there is a greater need to expedite the standardization of sample collection, processing, and bioinformatics in TMB assessment. Ethics Approval: This study was approved by the Providence St. Joseph Health Institutional Review Board, approval number STUDY2019000048.